Efeito agudo do exercício intervalado de alta intensidade sobre a pressão arterial de adolescentes com excesso de peso - Faria, Waynne Ferreira de (2016)
It has been shown that physical exercise is a non-pharmacological approach effective in the field of public health, since this is essential in the prevention, treatment and control of various morbidities. However, the type and dose of exercise required to induce health benefits, it is still a controversial issue. Therefore, the best clarification of the manipulation of the exercise prescription components in post-exercise hemodynamic responses in overweight and obesity is needed. The aim of this study was to analyze the BP behavior in adolescents with excess weight after a high intensity interval workout (HIT) on the treadmill. This is a study with cross-over randomized design the sample consisted of 11 male adolescents, 81.81% were obese and aged between 15 and 18 years. The nutritional status (BMI) was classified according to the criteria for age and sex of the World Health Organization. The volunteers performed two experimental protocols with a minimum interval of 48 hours: control and HIT. HIT protocol consisted of five series 85 to 95% of VO2peak for one minute, interleaved for three minutes of recovery at 40 to 50% VO2peak. Before and after the protocols, heart rate, systolic blood pressure (SBP) and diastolic and mean arterial pressure (MAP) were obtained in the sitting position. Ambulatory BP measurement was performed on two protocols through an automatic oscillometric monitor SpaceLabs 90207, scheduled to perform measurements every 20 minutes during wakefulness from 12:00 to 22:00 hours. The effects of experimental protocols on hemodynamic responses of adolescents were tested by analysis of variance for repeated measures, considering the factors (control and interval) and time (before and after the protocol). The results showed significant difference between the mean SBP in HIT and control protocols only in the first hour after the end of the exercise (131.90 ± 7.93 vs 124.18 ± 7.56 mmHg, respectively), indicating post-exercise hypotension induced by HIT compared to the control protocol. The comparison between the protocols and pre-session hemodynamic measurements and average post-session (10 hours) demonstrated that HIT was a mean decrease of 2 mmHg for MAP in comparison to pre-session (p < 0.05). Given the above, the results of this research suggest that in adolescents with excess weight, low-volume HIT protocol employed promoted hypotensive effect of low magnitude of the post-exercise on hemodynamic measures with regard to PAS and PAM.